Latissimus dorsi transfer for the treatment of massive tears of the rotator cuff - Zafra, Manuel (Springer-Verlag, 2008)
The objective of this paper was to determine the outcome of the transfer of the latissimus dorsi tendon in patients with massive irreparable rotator cuff tears. Eighteen patients of mean age 54 years (range 37–72 years) with massive irreparable rotator cuff tears were studied. The mean follow-up was 28 months (range 12–58 months). The postoperative Constant score was higher by an average of 21.15 points compared to the preoperative score (P=0.002); 88.8% of patients reported significant pain relief and improved mobility, particularly on external rotation. Postoperative resting antero-posterior radiography in neutral rotation revealed a mean 3.2-mm depression of the humeral head, due to the tenodesis effect of tendon transfer, thus, increasing the deltoid lever arm. These clinical results suggest that latissimus dorsi transfer is a useful surgical technique for treating massive irreparable postero-superior tears of the rotator cuff in young and/or active patients, providing significant pain relief and improved shoulder strength.